Kompensasi dan Motivasi Kerja dalam Mendorong Produktivitas Karyawan melalui Kepuasan Kerja sebagai Variabel Mediasi pada PT Maxim Indonesia - Hidayat, Rahmat; Setiawan, Aries; Libriantono, Bambang; Birawan, I Gusti Kade; Prastya Firmansyah, Ichsan (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2025)
This study aims to analyze the relationship between compensation and work motivation on employee productivity with job satisfaction as a mediating variable at PT Maxim. The research method uses a quantitative approach with a causal design. The research population consists of all employees of PT Maxim totaling 250 people, with a sample of 154 respondents selected using proportionate stratified random sampling. Data collection uses a questionnaire with a 5-point Likert scale, and data analysis uses Structural Equation Modeling based on Partial Least Squares with SmartPLS 4.0. The research results show that all hypotheses are accepted with good significance. Compensation and motivation have positive effects on productivity and job satisfaction. Job satisfaction has a positive effect on productivity. Job satisfaction partially mediates the relationship between compensation, motivation and employee productivity. The findings confirm that job satisfaction has a strategic role in enhancing the effectiveness of compensation and motivation on productivity. Managerial implications indicate the need for a holistic approach that integrates fair compensation systems, motivation enhancement programs, and job satisfaction strategies to optimize employee productivity sustainably.